Using Technology Acceptance Model 3 (TAM 3) at Selected Private Technical High School: Google Drive Storage in E-Learning - Setiyani, Lila; Effendy, Femmy; Slamet, Annisa Anggraini (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
During the Covid-19 pandemic, almost all schools around the world conduct the learning process by E-Learning courses. This brings consequences for various learning materials to be uploaded and stored in Google Drive. The purpose of this quantitative study was to determine the acceptance of Google Drive in E-Learning using the Technology Acceptance Model 3 (TAM 3) method at selected private vocational-technical high schools in Indonesia, i.e., STMIK Rosma. Sampling was conducted on 40 information system students at STMIK Rosma out of 83 student population using a proportionate stratified random sampling technique. Based on the results, students accepted Google Drive services in STMIK Rosma E-Learning with the following details, Subjective Norms (NS) had a significant influence on Image (CT) and Perceived Usefulness (KG), Image (CT) had a significant influence on Perceived Usefulness (KG), Perceived Enjoyment (KS) had a significant influence on Perceived Ease of Use (KP), and Perceived Ease of Use (KP) had a significant influence on Perceived Usefulness (KG). Thus, Google Drive is useful and needed in e-learning during the COVID-19 pandemic.